Public Participation in Adaptive Governance to Address the Climate Crisis in Dhaka, Bangladesh - Rahman, Mahbubur (Adaptive Governance Research, 2026)
Purpose: This study aims to examine the role of public participation within adaptive governance frameworks in addressing the climate crisis in Dhaka, Bangladesh. Specifically, it investigates how participatory mechanisms contribute to adaptive capacity, institutional learning, and climate-responsive decision-making in a highly vulnerable urban context, while also identifying the structural constraints that limit meaningful citizen influence on climate governance outcomes. Subjects and Methods: The research employed a qualitative case study design using semi-structured interviews, document analysis, and thematic analysis. Participants included government officials, NGOs, community leaders, and residents from climate-vulnerable areas in Dhaka. Results: The findings reveal that participatory practices primarily occur through consultations, workshops, and community meetings aimed at increasing climate awareness and preparedness. Participation contributed positively to community learning, collective action, and localized adaptive capacity. However, participatory governance remained largely procedural and consultative, with limited influence on strategic planning and policy decisions. Institutional fragmentation, bureaucratic rigidity, unequal representation, and weak accountability mechanisms significantly constrained the effectiveness of adaptive governance. Conclusions: The study concludes that public participation enhances localized resilience and procedural legitimacy but remains insufficient for transformative climate adaptation without stronger institutional coordination, inclusive representation, and long-term integration of community participation within formal governance systems.